2013
DOI: 10.5398/medpet.2013.36.2.101
|View full text |Cite
|
Sign up to set email alerts
|

The Success Rate of Artificial Insemination Using Post-Thawed Spotted Buffaloes Epididymal Sperm

Abstract: Spotted buffalo, an exotic species that exists in Tana Toraja, South Sulawesi, Indonesia, is getting extinct due to high number of slaughtered during a funeral ceremony, called Rambu Solo', as well as special treatments that do not allow the male spotted buffaloes perform natural mating activity. According to that, the research was trying to start conservation program by collected the cauda epididymal sperm soon after slaughtered. Two egg yolk-based extenders with different buffers, tris hydroxyl amino methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…The pregnancy rate obtained was lower than the result reported by Sianturi et al (2012) that found 77.8% in West Java's swamp buffaloes. However, the result was equal to that found in previous studies with pregnancy rate of 40%-60% (Batista et al, 2009;Yulnawati et al, 2013). Even in anoa, the post AI pregnancy rate was 25% (Judi et al, 2012) that was lower than result found in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…The pregnancy rate obtained was lower than the result reported by Sianturi et al (2012) that found 77.8% in West Java's swamp buffaloes. However, the result was equal to that found in previous studies with pregnancy rate of 40%-60% (Batista et al, 2009;Yulnawati et al, 2013). Even in anoa, the post AI pregnancy rate was 25% (Judi et al, 2012) that was lower than result found in this study.…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, a suitable semen freezing and handling technique needs to be developed. Using cauda epididymal spermatozoa, Yulnawati et al (2013) reported that tris-based and citrate-based extenders had similar ability to maintain the epididymal sperm quality and its fertilizing capacity in spotted buffalo. The addition of taurine or trehalose to the freezing extender was reported to reduce cryodamage in the buffalo spermatozoa (Reddy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%